1988
DOI: 10.1148/radiology.167.3.3363128
|View full text |Cite
|
Sign up to set email alerts
|

Cow's milk protein/soy protein allergy: gastrointestinal imaging.

Abstract: Positive radiologic findings were identified in the small and large bowels in three infants with various gastrointestinal manifestations of cow's milk protein/soy protein allergy, which was diagnosed on the basis of clinical features and histologic findings. Small bowel findings were thickened valvulae conniventes (plicae circulares), a ribbon-like ileum, and a thickened bowel wall. Narrowing, thumbprinting, and spasm were seen in the large bowel. These cases were seen at intervals far enough apart to exclude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…In all of them, contrast enema showed irregular narrowing of the rectum and a transitional zone, which required a differential diagnosis from Hirschsprung's disease. Richards et al [4] also reported a patient with rectal bleeding and whose contrast enema showed similar findings that Bloom et al reported. The contrast enema of the present case was quite similar to the findings of their reports.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In all of them, contrast enema showed irregular narrowing of the rectum and a transitional zone, which required a differential diagnosis from Hirschsprung's disease. Richards et al [4] also reported a patient with rectal bleeding and whose contrast enema showed similar findings that Bloom et al reported. The contrast enema of the present case was quite similar to the findings of their reports.…”
Section: Discussionsupporting
confidence: 72%
“…During the neonatal period, the most common presentation of allergic colitis is rectal bleeding [2], while Hirschsprung's disease-like symptoms are rarely reported [3][4][5]. We present a neonatal case of allergic colitis, which mimicked Hirschsprung's disease.…”
Section: Introductionmentioning
confidence: 94%
“…Two groups of reports are recognized, demonstrating unique imaging of spastic narrowing at the rectosigmoid, and duodeno-jejunal region. Some investigators reported contrast enema findings of neonatal and infant cases of allergic colitis showing segmental irregular narrowing of the rectum with a transition to dilated sigmoid colon, mimicking Hirschsprung's disease [8][9][10][11]. The rectal biopsies demonstrated ganglion cells with inflammatory infiltrates within the lamina propria, and suggested allergic origin [10].…”
Section: Discussionmentioning
confidence: 99%
“…Plain radiological imaging or imaging with barium contrast in infants with ongoing chronic symptoms of diarrhea, rectal bleeding, and/or failure to thrive revealed airfluid levels consistent with intestinal obstruction, nonspecific narrowing, and thumbprinting of the rectum and sigmoid, as well as thickening of the plicae circulares in the duodenum and jejunum with excess luminal fluid. Striking, ribbon-like jejunum with loss of plicae circulares and separation of bowel loops suggestive of thickening of the bowel wall has also been reported [69,70]. Distension of small bowel loops and marked jejunal wall thickening distal to the Treitz ligament with diffuse subserosal bleeding has been observed in extreme cases of ileus treated via laparotomy [69,71].…”
Section: Endoscopy and Biopsymentioning
confidence: 93%
“…FPIES is classified as a cellmediated disorder presumed to involve antigen-specific T lymphocytes, monocytes, antibodies, and cytokines as a cause of inflammation in the colon and, with variable degrees, the ileum [70,[91][92][93][94][95][96][97]. This inflammation is hypothesized to result in increased intestinal permeability leading to a fluid shift into the gastrointestinal lumen.…”
Section: Pathophysiologymentioning
confidence: 99%